Інноваційний розвиток економіки України: необхідність, реалії, перспективи - Пожуєва, Т.О. (Економічний вісник Донбасу, 2014)
В роботі акцентовано увагу на тому, що впровадження інноваційних технологій дає змогу підприємствам отримувати конкурентні переваги. Окрім того, проаналізовано інноваційну активність промислових підприємств України. В работе акцентировано внимание на то, что внедрение инновационных технологий дает возможность предприятиям получать конкурентные преимущества. Кроме того, проанализировано инновационную активность промышленных предприятий Украины. The problem of increasing of efficiency of innovative activity of domestic enterprises is getting fundamental importance in this difficult for Ukrainian market economy period, when such important tasks as the industrial complex saving, its restructuring and further technological development are appeared. Solving of this problem will get a possibility to create and use high-level technologies and therefore a possibility to accelerate growth of the national economy.
Ukraine’s economy continues to be immune to scientific and technological innovations due to low industry production base and weak state funding of scientific researches and engineering developments. That is why the formation of an effective state science and investment policies, which are addressed to achieve higher technological levels, should be based on the transformation of own researches and engineering developments to the basic element of production. The activation of innovation activity in scientific and industrial spheres is an important task for Ukraine and it is term of Ukraines economic independence.
The decreasing of number of scientists and research institutions is observed in Ukraine’s economy for the last ten years, those effects on the quantity and quality of innovative products. The share of completed scientific and technical works in GDP is continuously falling. The innovation activity of domestic enterprises in terms of general state support reduction is considered in this article.